A Literature Review on Tax Compliance in Indonesia In Increasing State Revenue - Ady Setyo Nugroho; Handayani, Nur (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2025)
Tax has long been one of the components of state revenue that cannot be separated from the life of society. Therefore, a supportive tax policy is needed. This policy should still consider all aspects that influence the lack of tax compliance. This research method is a literature review with a qualitative approach. The results obtained show that the factors impacting tax compliance are: 1) tax awareness; 2) perception of justice; 3) tax sanction enforcement; 4) economic factors; and 5) education factors.